2018
DOI: 10.1111/1911-3846.12393
|View full text |Cite
|
Sign up to set email alerts
|

Subjectivity in Professionals' Incentive Systems: Differences between Promotion‐ and Performance‐Based Assessments

Abstract: We examine how managers assess performance and promotion prospects—that is, the ex ante likelihood of promotion—and the conditions under which these assessments diverge. We argue that managers apply different cognitive schemas when they make different assessments. To the extent that a signal provides different information about future versus current contributions, assessed performance and promotion prospects are likely to diverge. In two experiments, we manipulate professionals' promotion eligibility and level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…In a meta-analysis study by Jawahar and Williams (1997), they found that evaluators give more lenient performance ratings when the ratings are used for compensation and promotion purposes, but give more accurate and harsher feedback for developmental purposes to help workers identify and correct their performance deficiencies. In addition, Bol and Leiby (2015) provide experimental evidence that managers evaluate the same actions taken by their subordinates differently when assessing their job performance versus their promotion prospects. These findings support the notion that evaluators assess workers' performance differently depending on the purpose of the performance evaluation.…”
Section: Advantagesmentioning
confidence: 99%
“…In a meta-analysis study by Jawahar and Williams (1997), they found that evaluators give more lenient performance ratings when the ratings are used for compensation and promotion purposes, but give more accurate and harsher feedback for developmental purposes to help workers identify and correct their performance deficiencies. In addition, Bol and Leiby (2015) provide experimental evidence that managers evaluate the same actions taken by their subordinates differently when assessing their job performance versus their promotion prospects. These findings support the notion that evaluators assess workers' performance differently depending on the purpose of the performance evaluation.…”
Section: Advantagesmentioning
confidence: 99%
“…Grabner and Moers [], Deller []). We proxy for promotability with supervisors’ perceptions of their subordinate's potential to be promoted to audit manager and audit partner (Bol and Leiby []) with promotability to manager (partner) being a relatively near‐term (long‐term) promotion. We test H1a by estimating the following logit model: truerightp()italicPotential=1=leftβ0+β10.16emitalicTK0.16emitalicSubordinate+β20.16emitalicJob0.16emitalicLevel+β30.16emitalicJob0.16emitalicTenureleft+0.16emβ40.16emAge+β50.16emTechnicalPerformance+ε,where Potential refers to either Potential Manager or Potential Partner .…”
Section: Results: Studymentioning
confidence: 99%
“…There are, however, other important indicators of value that are less backward looking (Cappelli and Tavis []). Bonuses capture contemporaneous value and are both tangible and salient, and promotability assessments capture forward‐looking value that tend to lead to the most significant lifetime compensation increases (Grabner and Moers [], Bol and Leiby []). With these three value indicators in mind, we hypothesize the following: H1a :Inexperienced auditors with higher versus lower tacit knowledge will be more highly valued. …”
Section: Background On Tacit Knowledge and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations